The Cross-cultural Experiences of International Secondary Students in Anglophone Countries: A Hermeneutic Literature Review and Conceptual Framework - Lou, Yingling (Journal of Interdisciplinary Studies in Education, 2023)
Prior to the pandemic, the number of international secondary students in anglophone countries had grown rapidly. Yet these minor transnational learners, most of whom unaccompanied, remain largely understudied and neglected in the educational research and policy discourses. This hermeneutic literature review addresses this profound literature gap by (a) identifying and synthesizing the available scholarly evidence on the cross-cultural experiences of international secondary students in anglophone countries, and (b) offering a critical analysis and assessment of the evidence that led to identification of knowledge and methodological gaps as well as implications for future studies. A conceptual framework was developed to provide a visual guideline of the cross-cultural adaptation process of the international secondary students. Findings of this article will be of value to researchers of international students and to educators serving international secondary students.